Genome-wide identification of genes encoding SWI/SNF components in soybean and the functional characterization of GmLFR1 in drought-stressed plants - Chen, Qiang; Shi, Xiaolei; Ai, Lijuan; Tian, Xuan; Zhang, Hongwei; Tian, Jiawang; Wang, Qianying; Zhang, Mengchen; Cui, Sujuan; Yang, Chunyan; Zhao, Hongtao (Frontiers in Plant Science, 2023)
ATP-dependent SWI/SNF chromatin remodeling complexes (CRCs) are evolutionarily conserved multi-component machines that regulate transcription, replication, and genome stability in eukaryotes. SWI/SNF components play pivotal roles in development and various stress responses in plants. However, the compositions and biological functions of SWI/SNF CRCs remain poorly understood in soybean. In this study, we used bioinformatics to identify 39 SWI/SNF CRC subunit-encoding genes distributed on the 19 chromosomes of soybean. The promoter regions of the genes were enriched with several cis-regulatory elements that are responsive to various hormones and stresses. Digital expression profiling and qRT-PCR revealed that most of the SWI/SNF genes were expressed in multiple tissues of soybean and were sensitive to drought stress. Phenotypical, physiological, and molecular genetic analyses revealed that GmLFR1 plays a negative role in drought tolerance in soybean. Together, our findings characterize putative components of soybean SWI/SNF CRCs and indicate possible roles for GmLFR1 in plants under drought stress. This study offers a foundation for comprehensive analyses of soybean SWI/SNF complexes and provides mechanistic insight into the epigenetic regulation of drought tolerance in soybean.